2015
DOI: 10.1021/acs.jpcc.5b01370
|View full text |Cite
|
Sign up to set email alerts
|

Tribocatalytic Reaction of Polytetrafluoroethylene Sliding on an Aluminum Surface

Abstract: To improve the tribological performance of polytetrafluoroethylene (PTFE) resin sliding against a metallic surface, it is important to understand the chemical behavior of PTFE in this sliding system. The tribochemical reaction of PTFE on an aluminum surface has been strenuously studied by a series of computational chemistry methods [Onodera, T., et al. J. Phys. Chem. C 2014, 118, 5390−5396, and Onodera, T., et al. J. Phys. Chem. C 2014, 118, 11820−11826]. One of the most important insights was that PTFE reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…[33] In addition, the formation mechanism of the tribo-film in the metal/PTFE tribo-pairs was investigated through a combination of experiments, density functional theory, and MD simulations. Their results indicated that the adsorption energy of the metal oxide interface, [34] the ionic bonding of the friction interface, [30] the friction-induced tribo-film, [29,30] and tribochemical reactants [35] may change the interface adhesion energy and play an important role in the formation of PTFE transfer membrane. The previous studies have mainly focused on the friction and wear behavior and potential lubrication mechanism of pure PTFE materials at nanoscale, but the molecular-scale reinforcement mechanism of the fillers in PTFE composites during friction is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[33] In addition, the formation mechanism of the tribo-film in the metal/PTFE tribo-pairs was investigated through a combination of experiments, density functional theory, and MD simulations. Their results indicated that the adsorption energy of the metal oxide interface, [34] the ionic bonding of the friction interface, [30] the friction-induced tribo-film, [29,30] and tribochemical reactants [35] may change the interface adhesion energy and play an important role in the formation of PTFE transfer membrane. The previous studies have mainly focused on the friction and wear behavior and potential lubrication mechanism of pure PTFE materials at nanoscale, but the molecular-scale reinforcement mechanism of the fillers in PTFE composites during friction is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In case of extreme pressure conditions (high load/temperature) PTFE chemically attached over the surface of steel ball in the form of metal fluoride. In this case, rate of removal of metallic part is faster than metal fluoride film formation Komvopoulos et al (2004), Onodera et al (2015), Onodera et al (2014) as shown in Figure 7(b). Indicate the reaching the dynamic equilibrium, resulting in marginal decrease in load bearing characteristics.…”
Section: Lubrication Mechanism Of Polytetrafluoroethylene and Moly Additivementioning
confidence: 89%
“…Thus, formation of Al−F species as well as the respective polyfluoroalkenes occur. Analogous behavior has been studied during the MC activation of PTFE with Al 2 O 3 [ 122 ]. Since the reaction barrier for a subsequent defluorination is too high, no further reductive dehalogenation reaction can be observed.…”
Section: Mechanochemical Decomposition Of Pfass and Involved Reactmentioning
confidence: 99%